Classification of lower limb range of motion values in futsal players - Cejudo, A.; Sainz de Baranda, P.; Ayala, F.; Santonja, F. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The purpose of this study was to quantitatively define the lower-limb values of range of motion in players of the 2nd Division of the <a href="https://www.google.es/url?sa=t&rct=j&q=&esrc=s&source=web&cd=3&cad=rja&uact=8&ved=0ahUKEwjQyPO9gazLAhUBVBQKHTvvBaQQFggtMAI&url=http%3A%2F%2Fenglandfutsal.com%2Fcategory%2Ffa-national-futsal-league%2F&usg=AFQjCNFuq3I_nEC3SFUzzF5G9KP-Acn1WQ&sig2=tp65b-olVD6M8VFNp1GnlQ">National Futsal League. Method: 60 players completed the basic version of the ROM-SPORT protocol. Descriptive and percentile analyses were carried out to establish the normative values for normal and limited mobility for each movement assessed. Results and conclusion: The present study defines the normative profile of the lower-limb range of motion in players of the 2nd Division LNFS in a range between 8-17º for hip extension, 39-45º for ankle flexion with knee extended, 40-47º for the ankle flexion with knee flexed, 42-47º for hip abduction, 76-96º for hip flexion with knee extended, 116-139º for knee flexion and 141-147º for the hip flexion. Values above the normal range may be considered within the optimal profile while lower values can be considered within the limited profile.